2017
DOI: 10.1161/circulationaha.116.023027
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Endothelial CXCR7 Impairs Vascular Homeostasis and Cardiac Remodeling After Myocardial Infarction

Abstract: CXCR7 represents a novel regulator of vascular homeostasis that functions in the endothelial compartment with sufficient capacity to affect cardiac function and remodeling after MI. Activation of CXCR7 may have therapeutic potential for clinical restenosis after percutaneous coronary intervention and for heart remodeling after MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
113
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 35 publications
4
113
0
Order By: Relevance
“…In our present study, we confirmed the similar biologic functions of CXCR7 in HRMEC by using shRNA-mediated genetic interference. Moreover, it has been reported that aberrant CXCR7 expression results in significant disruption of EC homeostatic functions, with a loss of contact inhibition and defects in endothelial barrier formation (44,45). These finding indicate that CXCR7 may be a potential target molecule for angiogenesis-dependent diseases.…”
Section: Discussionmentioning
confidence: 96%
“…In our present study, we confirmed the similar biologic functions of CXCR7 in HRMEC by using shRNA-mediated genetic interference. Moreover, it has been reported that aberrant CXCR7 expression results in significant disruption of EC homeostatic functions, with a loss of contact inhibition and defects in endothelial barrier formation (44,45). These finding indicate that CXCR7 may be a potential target molecule for angiogenesis-dependent diseases.…”
Section: Discussionmentioning
confidence: 96%
“…Deng et al have demonstrated that intercellular-adhesion-molecule-1-targeted microbubbles had successfully delivered the angiopoetin-1 gene to inflammatory endothelial cells and improved cardiac function of mice with myocardial infarction [25]. More recently, Hao et al reported that CXCR7, which is a chemokine receptor for CXCL12, was a key regulator for angiogenesis in the endothelium [26]. The information about transfected cells may be of value for future studies of the relationship between the therapeutic gene expression and their pharmacological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of endothelial normal function or structural integrity results in acute thrombosis, or chronic vascular changes that predispose to thrombosis among a variety of diseases, such as atherosclerosis, restenosis, diabetes mellitus, obesity, etc. [70][71][72][73] Understanding the mechanism by which endothelium regulates thrombosis not only provides insights into thrombosis mechanism and pathology of relevant diseases but also fuel the therapeutic endeavor for discovering effective antithrombotic drugs with minimal or no bleeding risk, which constitute a substantial unmet medical need.…”
Section: Discussionmentioning
confidence: 99%